Evaluating the Elemental Composition of Mature Human Milk: Implications for Infant Health in the Guadalajara Metropolitan Area - Peregrina Lucano, Alejandro Aarón; Aguilar Uscanga, Blanca Rosa; Solís Pacheco, Josué Raymundo; Rodríguez Arreola, Ariana (European Journal of Applied Sciences, 2024)
Environmental factors can significantly affect the health of infants through human milk, including the presence of toxic metals from various sources. In the metropolitan area of Guadalajara, current contamination levels are particularly concerning. Consequently, a study was conducted using Inductively Coupled Plasma Mass Spectrometry to analyze mature human milk from 30 housewives with various health issues. The results showed concentrations of toxic elements such as Pb, Zn, Cu, Hg, Cr, and As below 0.01 µg/L, while Al was above 0.51 µg/L and Cd above 0.7 µg/L. Additionally, variations were observed in essential elements such as Na, Mg, K, and Ca, with a notably high Na ratio in all cases, same case in Rb. In conclusion, this study revealed the presence of low concentrations of toxic metals in the breast milk of women from the metropolitan area of Guadalajara, except for Al and Cd. Significant variations in essential elements were also found, particularly a high Na ratio, which underlines the need to monitor environmental contaminants that may affect infant health through breastfeeding and identify their origin.